PENGARUH AKTIVITAS MATAHARI PADA KALA HIDUP SATELIT - Thomas Djamaluddin (Lembaga Penerbangan dan Antariksa Nasional, 2005)
It has been known the effect of solar activities in satellite orbits. However, kinds and magnitude of the effect should be investigated for developing integrated model on space weather and satellite orbits. This paper reports the result of global analysis of longterm orbiting satellite with lifetime several solar cycle. It is obtained that there is segregation on satellite's decay time indicating enhancement of satellite decay during active solar. Analysis result on some longterm orbiting satellite, covering several solar cycles, indicate a significant drop on orbital element during maximum solar activity.